DYING ARTERIOVENOUS FISTULAS - ALL IS NOT LOST YET! - Ali, Kishwar; Latif, Humera; Khan, Nauman Imtiaz; Butt, Hafiz Khalid Parvaiz; Khan, Rai Ahmad; Haider, Fazal e (Journal of Ayub Medical College Abbottabad, 2019)
Background: The aim of this study was to see the efficacy of different surgical procedures performed for the salvage of failing arteriovenous fistulas. Study design: Prospective observational study. Study was conducted at Department of Vascular surgery, CMH Rawalpindi from 1st August 2017 to 31st December 2018 Methods: Those surgical procedures were included which were done for the AVFs that failed to mature due to stealing veins or developed complications like thrombosis, hematoma, pseudo or true aneurysm, steal syndrome, stenosis and venous hypertension. The procedures like stealing vein ligation, hematoma evacuation, thrombectomies, redo-anastomosis, pseudo aneurysm excision, aneurysmorrhaphies, excision of stenotic segment, RUDI for steal syndrome and central veno venous bypasses for central vein occlusion were assessed for their efficacy. Results: Sixty-two patients were included. 21 stealing veins were ligated, 15 for fistula maturation and 6 for venous hypertension. Twelve out of these 15 non-maturing AVFs, matured after ligation of stealing vein (80%). In case of reverse vein ligation for venous hypertension all the 6 patients showed reduction in their limb swelling (100%). Nine thrombectomies were performed, 7 were successful (78%). Nine patients presented with stenosis. In 3 patients with stenosis near the anastomotic site, a proximal AVF was formed. In 2 patients the stenotic segment was excised and end to end anastomosis was done. In 1 patient an interposing vein graft was used. In 3 patients, the flow was redirected to basilic vein. All the patients had patent AVF on follow up (100%). In 8 non-infected pseudo aneurysms, excision and end to end anastomosis was done in 3, aneurysmorrhaphies in 2 and revision of the anastomosis in 3 cases. Seven out of 8 (87.5%) had good patency on follow up. In 7 patients with true aneurysm and 3 with bleeding from needle prick site sinus, aneurysmorrhaphies were performed. Two wound site hematomas were evacuated. Two patients presented with severe limb swelling due to central venous occlusion for whom a veno venous cross over bypass was done with good results. In 1 patient with steal syndrome, RUDI was done with acceptable results. Conclusion: Failing arteriovenous fistula can be salvaged by a variety of techniques provided that it is picked up in time. Keywords: Arteriovenous fistula; arteriovenous graft; fistula salvage